A comparison of two week versus two month anaesthetic training for internship doctors - Ash, Simon Alistair (My University, 2013)
BACKGROUND Since the inception of Community Service in 1998, junior doctors have been required to administer anaesthesia in rural areas with poor or no supervision, despite a lack of technical skills and an initial need for increased supervision. Up until the end of 2006, internship training included a two-week anaesthesia rotation. From 2007, the two-year internship was introduced in Gauteng, with new two-month anaesthesia rotation being instituted from 2008, as part of this two-year internship program. OBJECTIVES The aim of this study was to compare the adequacy of an internship doctor’s knowledge after two weeks versus two months of training in anaesthesia. The objectives of this study were to determine the anaesthetic knowledge of internship doctors completing a two-week and two-month anaesthetic rotation and compare their knowledge. METHOD After Wits Ethics Committee approval, 108 two-week interns (73% of the intern population) and 107 two-month interns (72% of the intern population) at the Witwatersrand Academic Complex were approached at the end of their internship (December 2006 and 2008 respectively). They completed a questionnaire in the form of short questions and case study vignettes, drawn up with a two-tier vetting process to assess basic anaesthetic knowledge as dictated by the Health Professions Council Of South Africa guidelines. Demographic data included the undergraduate institution and hospital where they had been trained. RESULTS The average result for the two-week interns was 38.95 (14.9) %. Knowledge of the anaesthetic machine check and anaesthetic pharmacology was inadequate (49% of respondents unable to describe the nitrous oxide pipeline, only 7% of respondents able to give the induction dose of Etomidate and 24% unable to list one contraindication to Suxamethonium). Analysis of variance showed a difference in the performance of respondents from the different WAC hospitals and undergraduate institutions. The average result for the two-month interns was 48.95 (21,77) %, an improvement of 10% overall. However, knowledge of the anaesthetic machine check and anaesthetic pharmacology remained inadequate (only 4% of respondents able to give the gauge pressure of a full oxygen cylinder, 63% of respondents unable to give the antidote for a benzodiazepine and 85% unable to give the induction dose of Etomidate). Analysis of variance again showed a difference in the performance of respondents from different undergraduate institutions, and further analysis of undergraduate institutions revealed that only three out of six institutions showed improvement between two weeks and two months of training in anaesthesia. CONCLUSION The following conclusions can be drawn from the study: 1) While the two-month anaesthesia rotation appears to improve the anaesthetic knowledge acquired during internship, increased exposure time alone may not be sufficient. Cognisance of other potential contributing factors should guide the design of the anaesthetic rotation so as to supplement potential shortfalls (e.g. undergraduate knowledge). 2) Anaesthetic knowledge after a two-month internship-training period, as assessed by our questionnaire, shows an improvement over the two-week training period, but still appears to be inadequate for the safe provision of unsupervised anaesthesia during Community Service.
Keywords: Anesthesiology--education